Analisis Manajemen Sember Daya Manusia Pada Pendidik Dan Tenaga Kependidikan Di Madrasah Aliyah Swasta Nurul Iman Desa Sidodadi Kecamatan Pardasuka Kabupaten Pringsewu Tahun Pelajaran 2023/2024 - Rusmela Dewi (Epsilon Journal of Management, 2024)
Many madrasahs are in the spotlight of the community regarding the quality of human resources of educators and education personnel, especially in madrasahs, this is because in addition to the very large number, the quality of management of educators and education personnel so far has not been able to be on par with other general education. However, madrasah institutions need to carry out strategies, one of which is the implementation of Planning, Organizing, Actuating, Controlling educators and education personnel continuously. The focus of this research is Human Empowerment Management in Educators and Education Personnel applied in Madrasah Aliyah Nurul Iman, in this case includes: Recruitment planning personal approach and selection that is not relevant to educational background. Organizing with placements that are directly arranged by the Head of the Foundation and the Head of Madrasah. Physical and non-physical movements through training are carried out periodically and control with the application of good discipline and dismissal is carried out if violations of discipline repeatedly. This research uses qualitative research with a case study design. Data and documents were collected and collected using in-depth interviews, participant observation and documentation studies The purpose of this study is to compare human empowerment management among educators and education personnel in Madrasah Aliyah Nurul Iman. The comparison aspects include the comparison of management of Educator Recruitment Planning, Organizing educators and education personnel. The most important subjects in the study were the head of the madrassa, the teachers, the madrasah committees of the two schools. Madrasah Aliyah Nurul Iman, has many similarities and differences in several aspects, therefore it is mandatory to improve the quality of the madrasah and is expected to be a treasure and input for the madrasah.